Necrobacillosis with pancytopenia. Issue 7 (July 1992) - Epstein, M; Pearson, A D; Hudson, S J; Bray, R; Taylor, M; Beesley, J
Abstract : Two young children whose presentation with necrobacillosis caused considerable diagnostic difficulty resulting in referral to an oncology unit are described. In both cases their severe suppurative multisystem illness was complicated by pancytopenia. One had bone marrow infarcts and severe endocarditis in addition to pulmonary involvement and the other had osteitis which resulted in a deformed humerus.